UPDATE HEALTH POLICY DECISION MAKING IN SAFE MOTHERHOOD REGIONAL ISSUE - Atmadja, Sardjana; Gumilar, Gulam (ADI Journal on Recent Innovation, 2020)
More than a half million women die every year because of complications related to pregnancy and child birth. Nearly all these deaths take place in developing countries. The disparity between maternal death rates in developing and developed countries is greater than for any other common category of death. Poor maternal health during pregnancy is directly linked to poor health in the infant. Therefore, a mother’s health and survival continues to be critically important throughout a child’s life. Pregnant women and children suffer first and most under poor socioeconomic conditions. To reduce maternal and morbidity in half by the 2000, the safe motherhood initiative was launched. The success of safe motherhood initiative depends on the active participation of a wide range of individuals and organizations who can contribute ideas, skills, and funds, because the problem stems not only from inadequate health services, but mostly also from the social, cultural, and economic environment in which women live. Health policy decision making in safe mother-hood at least should be based on the assessment of Maternal Health situation and health services and the assessment of socio- cultural aspects of safe motherhood of each region.